The complete chloroplast genome of Pleione formosana (Orchidaceae) - Ming-Tao Jiang; Wei-Chun Chao; Chun-Lin Huang; Si-Ren Lan; Zhong-Jian Liu; Sha-Sha Wu (Mitochondrial DNA. Part B. Resources, 2019)
Pleione formosana is an Endangered terrestrial orchid with significant ornamental values. Here, we report the first complete chloroplast genome of P. formosana. The circular genome was 159,843 bp in length and consisted of a pair of inverted repeats (IR 26,879 bp), which were separated by a large single copy region (LSC 87,392 bp) and a small single copy region (SSC 18,693 bp). It contained 135 genes (114 unique), including 87 protein-coding genes, 38 tRNAs, and 8 rRNAs. The maximum likelihood phylogenetic analysis indicated that P. formosana and P. bulbocodioides cluster together are closely related to the genera Bletilla.